Mergers and Acquisitions on Financial Performance of Commercial Banks in Kenya - Kyalo, Stanley D. (University of Embu, 2020)
Mergers and acquisitions have become the driving force of the world economy and have played strategy of many companies in the last decade. M&A are the strategic growth devices in the hands of more and more companies not only to stay in the competition but also to extend their margins, market share and dominance globally The scale and the pace at which merger activities are coming up are remarkable. From the last few decades, maximum studies focused to understand the importance of going into the deal of M&A. The current study examined motivation to recognize either the assumed benefits of the deal of M&A have posted increase or not. The current study calculated whether the deal is beneficial of harmful for the organizations who want to enter into the deal of M&A. The scrutinizes the issues by using the perspectives of history , waves, motives and methods to determine M&A value.The study focuses on the current literature available on M&A from the recent past to portray unlike the methods used to gauge performance of M&A. Although field of MMM&A research is far too broad and more complex to be covered in a review paper therefore, the study attempts to start covering some historical and background issues such as history, waves in M&A methods of measuring deals and M&A motives